Positive resist composition for extreme ultraviolet lithography and resist pattern forming kit for extreme ultraviolet lithography
Patent Information
- Application Number
- KR1020237007015
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-22
- Filing Date
- 2021-09-15
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2041-09-15
Smart Images

Figure 112023022754188-PCT00013_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a positive-type resist composition for extreme ultraviolet lithography and a resist pattern forming kit for extreme ultraviolet lithography. Background Technology
[0002] Conventionally, in fields such as semiconductor manufacturing, copolymers whose main chains are cleaved by irradiation with ionizing radiation such as electron beams or short-wavelength light such as ultraviolet rays (hereinafter, ionizing radiation and short-wavelength light are collectively referred to as "ionizing radiation, etc.") and whose solubility in a developer is increased are used as main chain-cleaved positive type resists.
[0003] Specifically, for example, Patent Document 1 discloses a positive resist comprising a copolymer containing α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and α-methylstyrene units, as a main chain cleavage type positive resist having excellent sensitivity to ionizing radiation and heat resistance. Prior art literature
[0004] Japanese Patent Publication No. 2018-154754 The problem to be solved
[0005] In recent years, EUV lithography technology using extreme ultraviolet (EUV) has garnered attention as a technique that enables the formation of fine patterns with minimal proximity effects during exposure compared to electron beams and the like. Meanwhile, the aforementioned conventional technology had room for improvement in terms of enabling the efficient formation of fine resist patterns at high resolution when using extreme ultraviolet as a light source for exposure.
[0006] Accordingly, the present invention aims to provide a positive resist composition and a resist pattern forming kit that can be used to efficiently form fine resist patterns at high resolution in EUV lithography technology.
[0007] Meanwhile, in the present invention, "high resolution" refers to a condition in which surface roughness or the occurrence of missing contact holes on the surface of the exposed area after development is suppressed, and evaluation results such as CD value (Critical Dimension value: a value indicating the limit dimension of the line width of the resist pattern), LWR value (Line Width Roughness value: a value indicating line width roughness), LER value (Line Edge Roughness value: a value indicating the edge roughness), and LCDU value (Local Critical Dimension Uniformity value: uniformity of the local limit dimension) are good. means of solving the problem
[0008] The inventors have conducted thorough investigations to achieve the above objective. Furthermore, the inventors have discovered that by using a copolymer formed using a predetermined monomer, wherein the weight-average molecular weight is within a predetermined range, fine resist patterns can be efficiently formed at high resolution in EUV lithography technology, thereby completing the present invention.
[0009] That is, the present invention aims to advantageously solve the above problem, and the positive type resist composition for extreme ultraviolet lithography of the present invention is the following formula (I):
[0010] [Chemical Formula 1]
[0011]
[0012] [In formula (I), X is a halogen atom, a cyano group, an alkylsulfonyl group, an alkoxy group, a nitro group, an acyl group, an alkyl ester group, or an alkyl halide group; L is a single bond or a divalent linker; and Ar is an aromatic ring that may have a substituent.]
[0013] A monomer unit (A) represented by, and the following formula (II):
[0014] [Chemical Formula 2]
[0015]
[0016] [In Equation (II), R 1 It is an alkyl group, and R 2 is an alkyl group, a halogen atom, an alkyl halide, a hydroxyl group, a carboxyl group, or a carboxyl halide, and p is an integer between 0 and 5 inclusive, and R 2 If there are multiple instances of 'a', they may be identical or different from each other.
[0017] It is characterized by including a copolymer having a monomer unit (B) represented by, and a weight average molecular weight greater than 100,000.
[0018] The copolymer having the above monomer unit (A) and monomer unit (B) can be well used as a main chain cleavage type positive type resist. In addition, if the weight average molecular weight of the copolymer having the monomer unit (A) and monomer unit (B) is greater than 100,000, when used in EUV lithography, a fine resist pattern can be efficiently formed at high resolution.
[0019] Meanwhile, in the present invention, the “weight average molecular weight” can be measured as a standard polystyrene equivalent value using gel permeation chromatography.
[0020] Here, in the positive resist composition for extreme ultraviolet lithography according to the present invention, the monomer unit (A) is preferably an α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl unit, and the monomer unit (B) is preferably an α-methylstyrene unit or a 4-methyl-α-methylstyrene unit. If the copolymer has the monomer units described above, the sensitivity to EUV can be sufficiently improved, and at the same time, a fine resist pattern can be formed more effectively.
[0021] In addition, in the positive type resist composition for extreme ultraviolet lithography according to the present invention, it is preferable that the copolymer has a content ratio of the monomer unit (A) of more than 50 mol% and less than or equal to 60 mol%, and a content ratio of the monomer unit (B) of more than 40 mol% and less than or equal to 50 mol%. If the ratio of the monomer unit (A) and the monomer unit (B) of the copolymer is within the above range, a fine resist pattern can be formed more efficiently and at high resolution when used in EUV lithography.
[0022] In addition, in the positive type resist composition for extreme ultraviolet lithography of the present invention, it is preferable that the copolymer has a molecular weight distribution (Mw / Mn) of 1.20 or more and 1.60 or less.
[0023] Here, in the present invention, the “molecular weight distribution” can be obtained by calculating the ratio of the weight-average molecular weight to the number-average molecular weight (weight-average molecular weight / number-average molecular weight), and the “number-average molecular weight” can be measured as a standard polystyrene equivalent value using gel permeation chromatography.
[0024] In addition, in the positive type resist composition for extreme ultraviolet lithography according to the present invention, it is preferable that the copolymer has a ratio of a component with a molecular weight of less than 10,000 of less than 1.5%. If the ratio of a component with a molecular weight of less than 10,000 is within the above range, a fine resist pattern can be formed more efficiently and at high resolution when used in EUV lithography.
[0025] Meanwhile, in the present invention, the “ratio of components with a molecular weight of less than 10,000” can be obtained by using a chromatogram obtained by gel permeation chromatography and calculating the ratio (= (B / A) × 100%) of the sum of the peak areas of components with a molecular weight of less than 10,000 in the chromatogram to the total peak area (A) in the chromatogram.
[0026] In addition, in the positive type resist composition for extreme ultraviolet lithography according to the present invention, it is preferable that the copolymer has a ratio of components with a molecular weight of less than 50,000 of less than 30%. If the ratio of components with a molecular weight of less than 50,000 is within the above range, fine resist patterns can be formed more efficiently and at high resolution when used in EUV lithography.
[0027] Meanwhile, in the present invention, the “ratio of components with a molecular weight of less than 50,000” can be obtained by using a chromatogram obtained by gel permeation chromatography and calculating the ratio (= (C / A) × 100%) of the sum of the peak areas of components with a molecular weight of less than 50,000 in the chromatogram to the total peak area (A) in the chromatogram.
[0028] In addition, in the positive type resist composition for extreme ultraviolet lithography according to the present invention, it is preferable that the copolymer has a ratio of components with a molecular weight of less than 100,000 of less than 70%. If the ratio of components with a molecular weight of less than 100,000 is within the above range, fine resist patterns can be formed more efficiently and at high resolution when used in EUV lithography.
[0029] Meanwhile, in the present invention, the “ratio of components with a molecular weight of less than 100,000” can be obtained by using a chromatogram obtained by gel permeation chromatography and calculating the ratio (= (D / A) × 100%) of the sum of the peak areas of components with a molecular weight of less than 100,000 in the chromatogram to the total peak area (A) in the chromatogram.
[0030] In addition, in the positive type resist composition for extreme ultraviolet lithography according to the present invention, it is preferable that the copolymer has a ratio of a component with a molecular weight greater than 200,000 of 8.0% or more. If the ratio of a component with a molecular weight greater than 200,000 is within the above range, a fine resist pattern can be formed more efficiently and at high resolution when used in EUV lithography.
[0031] Meanwhile, in the present invention, the “ratio of components with a molecular weight greater than 200,000” can be obtained by using a chromatogram obtained by gel permeation chromatography and calculating the ratio (= (E / A) × 100%) of the sum of the peak areas of components with a molecular weight greater than 200,000 in the chromatogram to the total peak area (A) in the chromatogram.
[0032] Furthermore, the present invention aims to advantageously solve the above problem. The resist pattern forming kit for extreme ultraviolet lithography according to the present invention is characterized by comprising any one of the positive-type resist compositions for extreme ultraviolet lithography described above and a developer. When the resist pattern forming kit comprising the positive-type resist composition for extreme ultraviolet lithography described above and a developer is used in EUV lithography, fine resist patterns can be efficiently formed at high resolution.
[0033] Here, in the resist pattern forming kit for extreme ultraviolet lithography according to the present invention, the developer is preferably an alcohol, and more preferably an alcohol having 2 to 6 carbon atoms. When an alcohol, preferably an alcohol having 2 to 6 carbon atoms, is used as the developer, a fine resist pattern can be formed more efficiently and at a high resolution by EUV lithography. Effects of the invention
[0034] According to the present invention, it is possible to efficiently form fine resist patterns at high resolution in EUV lithography technology. Specific details for implementing the invention
[0035] Hereinafter, embodiments of the present invention will be described in detail.
[0036] Meanwhile, in the present invention, "may have a substituent" means "non-substituent, or having a substituent."
[0037] Here, the positive-type resist composition for EUV lithography according to the present invention is used for forming a resist film when forming a resist pattern using extreme ultraviolet rays, which have a smaller proximity effect during exposure compared to electron beams, etc., and also enable the formation of fine patterns. Furthermore, the EUV lithography resist pattern forming kit according to the present invention comprises the positive-type resist composition for EUV lithography according to the present invention and can be suitably used when forming a resist pattern using extreme ultraviolet rays in a manufacturing process of a printed circuit board, such as a build-up substrate, for example.
[0038] (Positive resist composition for EUV lithography)
[0039] The positive-type resist composition for EUV lithography according to the present invention comprises a predetermined copolymer described in detail below and typically further contains a solvent. Additionally, the positive-type resist composition for EUV lithography further contains a known additive that may optionally be incorporated into the resist composition.
[0040] In addition, since the positive-type resist composition for EUV lithography according to the present invention contains a predetermined copolymer as a positive-type resist, a fine resist pattern can be efficiently formed at high resolution by using a resist film obtained by applying and drying the positive-type resist composition on a substrate.
[0041] Meanwhile, the positive resist composition for EUV lithography according to the present invention may contain a polymer other than a predetermined copolymer as a positive resist, but typically contains only a predetermined copolymer as a positive resist.
[0042] Copolymer
[0043] The copolymer included in the positive type resist composition of the present invention has a predetermined monomer unit (A) and monomer unit (B) and has a weight average molecular weight of more than 100,000.
[0044] Meanwhile, the copolymer of the present invention may include any monomer unit other than monomer unit (A) and monomer unit (B), but the proportion of monomer unit (A) and monomer unit (B) among the total monomer units constituting the copolymer is preferably 90 mol% or more in total, and more preferably 100 mol% (i.e., the copolymer contains only monomer unit (A) and monomer unit (B)).
[0045] [Monomer Unit (A)]
[0046] Here, the monomer unit (A) is given by the following formula (I):
[0047] [Chemical Formula 3]
[0048]
[0049] [In formula (I), X is a halogen atom, a cyano group, an alkylsulfonyl group, an alkoxy group, a nitro group, an acyl group, an alkyl ester group, or an alkyl halide group; L is a single bond or a divalent linker; and Ar is an aromatic ring that may have a substituent.]
[0050] It is represented as, and the following equation (III):
[0051] [Chemical Formula 4]
[0052]
[0053] It is a structural unit derived from monomer (a) represented by [wherein X, L, and Ar are identical to those in Formula (I).]
[0054] Here, halogen atoms that can constitute X in formulas (I) and (III) may include, for example, chlorine atoms, fluorine atoms, bromine atoms, iodine atoms, or astatine atoms. Additionally, alkylsulfonyl groups that can constitute X in formulas (I) and (III) may include, for example, methylsulfonyl groups or ethylsulfonyl groups. Additionally, alkoxy groups that can constitute X in formulas (I) and (III) may include, for example, methoxy groups, ethoxy groups, or propoxy groups. Additionally, acyl groups that can constitute X in formulas (I) and (III) may include formyl groups, acetyl groups, or propionyl groups. Additionally, alkyl ester groups that can constitute X in formulas (I) and (III) may include methyl ester groups or ethyl ester groups. In addition, alkyl halide groups that can constitute X in formulas (I) and (III) may include, for example, methyl halide groups having 1 or more and 3 or fewer halogen atoms.
[0055] Among these, from the perspective of efficiently obtaining a copolymer useful as a main chain cleavage type positive resist, it is preferable that X be a halogen atom, and more preferable that X be a chlorine atom.
[0056] In addition, the divalent linker that can constitute L in formulas (I) and (III) is not particularly limited and, for example, may include an alkylene group that may have a substituent, an alkenylene group that may have a substituent, etc.
[0057] In addition, the alkylene groups that may have substituents are not particularly limited, and examples include chain-type alkylene groups such as methylene groups, ethylene groups, propylene groups, n-butylene groups, and isobutylene groups, and cyclic alkylene groups such as 1,4-cyclohexylene groups. Among these, as for the alkylene groups, chain-type alkylene groups having 1 to 6 carbon atoms, such as methylene groups, ethylene groups, propylene groups, n-butylene groups, and isobutylene groups, are preferred; straight-chain alkylene groups having 1 to 6 carbon atoms, such as methylene groups, ethylene groups, propylene groups, and n-butylene groups, are more preferred; and straight-chain alkylene groups having 1 to 3 carbon atoms, such as methylene groups, ethylene groups, and propylene groups, are even more preferred.
[0058] In addition, the alkenylene groups that may have substituents are not particularly limited, and examples include chain-type alkenylene groups such as ethenylene groups, 2-propenylene groups, 2-butenylene groups, and 3-butenylene groups, and cyclic alkenylene groups such as cyclohexanylene groups. Among these, as the alkenylene groups, straight-chain alkenylene groups having 2 to 6 carbon atoms, such as ethenylene groups, 2-propenylene groups, 2-butenylene groups, and 3-butenylene groups, are preferred.
[0059] Among the above, from the perspective of sufficiently improving sensitivity to EUV, as for the divalent linker, an alkylene group that may have a substituent is preferred, a chain-type alkylene group having 1 to 6 carbon atoms that may have a substituent is more preferred, a straight-chain alkylene group having 1 to 6 carbon atoms that may have a substituent is even more preferred, and a straight-chain alkylene group having 1 to 3 carbon atoms that may have a substituent is particularly preferred.
[0060] In addition, from the perspective of further improving sensitivity to EUV, it is desirable that the divalent linker capable of constituting L in Formulas (I) and (III) has one or more electron-withdrawing groups. Among these, when the divalent linker is an alkylene group having an electron-withdrawing group as a substituent or an alkenylene group having an electron-withdrawing group as a substituent, it is desirable that the electron-withdrawing group is bonded to a carbon that is bonded to O adjacent to the carbonyl carbon in Formulas (I) and (III).
[0061] Meanwhile, electron-withdrawing groups capable of sufficiently improving sensitivity to EUV are not particularly limited, and for example, at least one selected from the group consisting of fluorine atoms, fluoroalkyl groups, cyano groups, and nitro groups may be cited. In addition, fluoroalkyl groups are not particularly limited, and for example, fluoroalkyl groups having 1 to 5 carbon atoms may be cited. Among these, perfluoroalkyl groups having 1 to 5 carbon atoms are preferred as fluoroalkyl groups, and trifluoromethyl groups are more preferred.
[0062] And, from the perspective of sufficiently improving sensitivity to EUV, L in formulas (I) and (III) is preferably a methylene group, a cyanomethylene group, a trifluoromethylmethylene group, or a bis(trifluoromethyl)methylene group, and a bis(trifluoromethyl)methylene group is more preferable.
[0063] In addition, Ar in formulas (I) and (III) may include aromatic hydrocarbon groups that may have substituents and aromatic complex groups that may have substituents.
[0064] In addition, aromatic hydrocarbon groups are not particularly limited and examples include benzene groups, biphenyl groups, naphthalene groups, azulene groups, anthracene groups, phenanthrene groups, pyrene groups, chrysene groups, naphthacene groups, triphenylene groups, o-terphenyl groups, m-terphenyl groups, p-terphenyl groups, acenaphthene groups, coronene groups, fluorene groups, fluoranthrene groups, pentacene groups, perylene groups, pentaphene groups, physene groups, pyranthrene groups, etc.
[0065] In addition, aromatic complex groups are not particularly limited and include, for example, furan groups, thiophene groups, pyridine groups, pyridazine groups, pyrimidine groups, pyrazine groups, triazine groups, oxadiazole groups, triazole groups, imidazole groups, pyrazol groups, thiazole groups, indole groups, benzimidazole groups, benzothiazole groups, benzoxazole groups, quinoxaline groups, quinazolin groups, phthalazine groups, benzofuran groups, dibenzofuran groups, benzothiophene groups, dibenzothiophene groups, carbazole groups, etc.
[0066] In addition, the substituents that Ar can have are not particularly limited, and examples include alkyl groups, fluorine atoms, and fluoroalkyl groups. Also, alkyl groups that Ar can have as substituents include, for example, chain-type alkyl groups having 1 to 6 carbon atoms, such as methyl groups, ethyl groups, propyl groups, n-butyl groups, and isobutyl groups. In addition, fluoroalkyl groups that Ar can have as substituents include, for example, fluoroalkyl groups having 1 to 5 carbon atoms, such as trifluoromethyl groups, trifluoroethyl groups, and pentafluoropropyl groups.
[0067] Among these, from the perspective of sufficiently improving sensitivity to EUV, for Ar in formulas (I) and (III), an aromatic hydrocarbon group that may have a substituent is preferred, an unsubstituted aromatic hydrocarbon group is more preferred, and a benzene group (phenyl group) is even more preferred.
[0068] And, from the perspective of sufficiently improving sensitivity to EUV, the monomer (a) represented by the formula (III) described above, which can form the monomer unit (A) represented by the formula (I) described above, is preferably α-chloroacrylate benzyl and α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl, and more preferably α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl. That is, the copolymer is preferably to have at least one of the α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl unit and the α-chloroacrylate benzyl unit, and more preferably to have the α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl unit.
[0069] Meanwhile, the proportion of monomer units (A) among the total monomer units constituting the copolymer is not particularly limited and can be, for example, 30 mol% or more and 70 mol% or less. Among these, the proportion of monomer units (A) is preferably 50 mol% or more, more preferably greater than 50 mol%, even more preferably 52 mol% or more, preferably 60 mol% or less, more preferably 55 mol% or less, and even more preferably 54 mol% or less. If the proportion of monomer units (A) is within the above range, fine resist patterns can be formed more efficiently and at high resolution when used in EUV lithography.
[0070] [Monomer Unit (B)]
[0071] The monomer unit (B) is the following formula (II):
[0072] [Chemical Formula 5]
[0073]
[0074] [In Equation (II), R 1 It is an alkyl group, and R 2is an alkyl group, a halogen atom, an alkyl halide, a hydroxyl group, a carboxyl group, or a carboxyl halide (-C(=O)-X; X is a halogen atom), p is an integer between 0 and 5, and R 2 If there are multiple instances of 'a', they may be identical or different from each other.
[0075] It is represented as, and the following equation (IV):
[0076] [Chemical Formula 6]
[0077]
[0078] [In Equation (IV), R 1 and R 2 , and, p is the same as in formula (II).] is a structural unit derived from monomer (b).
[0079] Here, R in Equations (II) and (IV) 1 ~ R 2 The alkyl groups that can constitute are not particularly limited, and examples include unsubstituted alkyl groups having 1 to 5 carbon atoms. Among these, R 1 ~ R 2 As for the alkyl groups that can constitute it, methyl or ethyl groups are preferred.
[0080] Also, R in Equation (II) and Equation (IV) 2 The halogen atoms that can constitute it are not particularly limited and include fluorine atoms, chlorine atoms, bromine atoms, iodine atoms, etc. Among these, fluorine atoms are preferred as halogen atoms.
[0081] Also, R in Equation (II) and Equation (IV) 2 The alkyl halide groups that can constitute the group are not particularly limited, and examples include fluoroalkyl groups having 1 to 5 carbon atoms. Among these, perfluoroalkyl groups having 1 to 5 carbon atoms are preferred as alkyl halide groups, and trifluoromethyl groups are more preferred.
[0082] Also, R in Equation (II) and Equation (IV) 2 Halogenated carboxyl groups that can constitute the structure are not particularly limited, and examples include chloride carboxyl groups (-C(=O)-Cl), fluoride carboxyl groups (-C(=O)-F), bromide carboxyl groups (-C(=O)-Br), etc.
[0083] And, in terms of improving the ease of preparation of the copolymer and the cleavage of the main chain when irradiated with EUV, R in Formulas (II) and (IV) 1 It is preferable that the silver be an alkyl group having 1 to 5 carbon atoms, and more preferable that it be a methyl group.
[0084] In addition, from the perspective of improving the ease of preparation of the copolymer and the cleavage of the main chain when irradiated with EUV, it is preferable that p in formulas (II) and (IV) be 0 or 1.
[0085] In addition, if p in Equations (II) and (IV) is any one of 1 to 5, R in Equations (II) and (IV) 2 It is preferably an alkyl group having 1 to 5 carbon atoms, and more preferably a methyl group.
[0086] And, the monomer (b) represented by the formula (IV) described above, which can form the monomer unit (B) represented by the formula (II) described above, is not particularly limited and, for example, α-methylstyrene and its derivatives such as (b-1) to (b-12) below may be cited.
[0087] [Chemical Formula 7]
[0088]
[0089] Meanwhile, from the perspective of improving the ease of preparation of the copolymer and the cleavage of the main chain when irradiated with EUV, it is preferable that the monomer unit (B) be a structural unit derived from α-methylstyrene or 4-methyl-α-methylstyrene. That is, it is preferable that the copolymer have α-methylstyrene units or 4-methyl-α-methylstyrene units.
[0090] In addition, the proportion of monomer units (B) among the total monomer units constituting the copolymer is not particularly limited and can be, for example, 30 mol% or more and 70 mol% or less. Among these, the proportion of monomer units (B) is preferably 40 mol% or more, more preferably 45 mol% or more, even more preferably 46 mol% or more, preferably 50 mol% or less, more preferably less than 50 mol%, and even more preferably 48 mol% or less. If the proportion of monomer units (B) is within the above range, fine resist patterns can be formed more efficiently and at high resolution when used in EUV lithography.
[0091] [Properties of the copolymer]
[0092] In addition, the copolymer needs to have a weight average molecular weight (Mw) greater than 100,000, and the weight average molecular weight of the copolymer is preferably 110,000 or more, more preferably 150,000 or more, and even more preferably 200,000 or more. If the weight average molecular weight of the copolymer is within the above range, fine resist patterns can be efficiently formed at high resolution when used in EUV lithography.
[0093] Meanwhile, although the upper limit of the weight-average molecular weight of the copolymer is not particularly limited, from the perspective of suppressing difficulty in filtration when preparing a positive-type resist composition, it is preferable that it be 500,000 or less, and more preferable that it be 210,000 or less.
[0094] In addition, the number average molecular weight (Mn) of the copolymer is preferably 70,000 or higher, more preferably 110,000 or higher, even more preferably 130,000 or higher, preferably 400,000 or lower, more preferably 300,000 or lower, and even more preferably 140,000 or lower. If the number average molecular weight of the copolymer is greater than or equal to the lower limit value above, a fine resist pattern can be efficiently formed at high resolution when used in EUV lithography. In addition, if the number average molecular weight of the copolymer is less than or equal to the upper limit value above, it is easy to prepare a positive-type resist composition.
[0095] In addition, the molecular weight distribution (Mw / Mn) of the copolymer is preferably 1.20 or higher, more preferably 1.25 or higher, even more preferably 1.30 or higher, preferably 2.00 or lower, more preferably 1.90 or lower, even more preferably 1.60 or lower, even more preferably 1.50 or lower, and particularly preferably 1.40 or lower.
[0096] In addition, from the perspective of more efficiently forming fine resist patterns at high resolution when using a positive type resist composition in EUV lithography, it is preferable that the copolymer satisfies at least one of the following (1) to (4), and more preferable that it satisfies all of (1) to (4).
[0097] (1) The proportion of a component with a molecular weight of less than 10,000 is less than 1.5%, preferably 1.3% or less, more preferably 0.5% or less, even more preferably 0.25% or less, even more preferably 0.15% or less, and particularly preferably 0.08% or less. Meanwhile, the proportion of a component with a molecular weight of less than 10,000 is not particularly limited, but, for example, 0.0001% or more, and may be 0.0003% or more.
[0098] (2) The proportion of the component with a molecular weight of less than 50,000 is less than 30%, preferably 20% or less, more preferably 5% or less, even more preferably 1% or less, and particularly preferably 0.4% or less. Meanwhile, the proportion of the component with a molecular weight of less than 50,000 is not particularly limited, but, for example, 0.01% or more, and may be 0.05% or more.
[0099] (3) The proportion of the component with a molecular weight of less than 100,000 is less than 70%, preferably 65% or less, more preferably 30% or less, even more preferably 10% or less, even more preferably 5% or less, particularly preferably 2% or less. Meanwhile, the proportion of the component with a molecular weight of less than 100,000 is not particularly limited, but, for example, 0.1% or more, and may be 0.5% or more.
[0100] (4) The proportion of the component with a molecular weight greater than 200,000 is greater than 8.0%, preferably 30% or more, more preferably 50% or more, even more preferably 60% or more, and particularly preferably 85% or more. Meanwhile, the proportion of the component with a molecular weight greater than 200,000 is not particularly limited, but, for example, 99% or less, and may be 95% or less.
[0101] [Method for preparing copolymer]
[0102] In addition, a copolymer having the monomer unit (A) and monomer unit (B) described above can be prepared, for example, by polymerizing a monomer composition comprising monomer (a) and monomer (b), recovering the obtained copolymer, and optionally purifying it.
[0103] Meanwhile, the composition, molecular weight distribution, weight-average molecular weight, and number-average molecular weight of the copolymer can be adjusted by changing the polymerization method, polymerization conditions (e.g., polymerization temperature, polymerization time, and the type and amount of polymerization initiator, etc.), and purification conditions. Specifically, for example, the weight-average molecular weight and number-average molecular weight can be increased by lowering the polymerization temperature. Additionally, the weight-average molecular weight and number-average molecular weight can be increased by shortening the polymerization time. Furthermore, the molecular weight distribution can be reduced by performing purification.
[0104] Here, as the monomer composition used for preparing the copolymer, a mixture of a monomer component including monomer (a) and monomer (b), an optionally usable solvent, an optionally usable polymerization initiator, and an optionally added additive may be used. Furthermore, the polymerization of the monomer composition may be carried out using known methods, such as solution polymerization or emulsion polymerization. Among these, it is preferable to use cyclopentanone, water, etc., as the solvent. In addition, it is preferable that the amount of polymerization initiator be 0 (zero).
[0105] In addition, the polymer obtained by polymerizing the monomer composition may be used as a copolymer as is, but is not particularly limited, and can be recovered by adding a solvent such as tetrahydrofuran to a solution containing the polymer, and then dropping the solution with added solvent into a non-solvent such as methanol to coagulate the polymer.
[0106] Meanwhile, the purification method used to purify the obtained polymer is not particularly limited, and known purification methods such as reprecipitation or column chromatography may be used. Among these, it is preferable to use the reprecipitation method as the purification method.
[0107] Meanwhile, the purification of the polymer may be repeated multiple times.
[0108] Furthermore, purification of the polymer by the reprecipitation method is preferably carried out by, for example, dissolving the obtained polymer in a solvent such as tetrahydrofuran, and then adding the resulting solution dropwise to a mixed solvent of a solvent such as tetrahydrofuran and a solvent such as methanol to precipitate a portion of the polymer. In this way, purification is performed by adding the polymer solution dropwise to a mixed solvent of a solvent and a solvent, thereby allowing the molecular weight distribution, weight average molecular weight, and number average molecular weight of the obtained copolymer to be easily adjusted by changing the types of solvents and solvents or the mixing ratio. Specifically, for example, the molecular weight of the copolymer precipitated in the mixed solvent can be increased as the ratio of the solvent in the mixed solvent increases.
[0109] Meanwhile, when purifying the polymer by the reprecipitation method, as the copolymer, provided that the desired properties are satisfied, a polymer precipitated in a mixed solvent of both solvents and a co-solvent may be used, or a polymer that has not precipitated in the mixed solvent (i.e., a polymer dissolved in the mixed solvent) may be used. Here, the polymer that has not precipitated in the mixed solvent can be recovered from the mixed solvent using known methods such as concentration and drying.
[0110] Solvent
[0111] The solvent included in the positive-type resist composition for EUV lithography is not particularly limited as long as it is a solvent capable of dissolving the copolymer described above, and known solvents such as the solvent described in Japanese Patent No. 5938536 may be used. Among these, from the perspective of obtaining a positive-type resist composition of suitable viscosity and improving the coating properties of the positive-type resist composition, it is preferable to use anisole, propylene glycol monomethyl ether acetate (PGMEA), cyclopentanone, cyclohexanone, or isoamyl acetate as the solvent.
[0112] <EUV 리소그래피용 포지티브형 레지스트 조성물의 조제>
[0113] A positive-type resist composition for EUV lithography can be prepared by mixing the aforementioned copolymer, a solvent, and optionally known additives. At that time, the mixing method is not particularly limited and may be mixed by a known method. Additionally, the composition may be prepared by filtering the mixture after mixing each component.
[0114] [percolation]
[0115] Here, the method of filtration of the mixture is not particularly limited and, for example, can be filtered using a filter. The filter is not particularly limited and, for example, filtration membranes such as fluorocarbon-based, cellulose-based, nylon-based, polyester-based, and hydrocarbon-based filters may be used. Among these, in order to effectively prevent impurities such as metal from metal pipes used during the preparation of copolymers from being incorporated into the positive-type resist composition, polyfluorocarbons such as nylon, polyethylene, polypropylene, polytetrafluoroethylene, and Teflon (registered trademark), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), nylon, and composite membranes of polyethylene and nylon are preferred as materials constituting the filter. As a filter, for example, the one disclosed in U.S. Patent No. 6103122 may be used. In addition, the filter is commercially available as Zeta Plus (registered trademark) 40Q manufactured by CUNO Incorporated. In addition, the filter may comprise a strongly cationic or weakly cationic ion exchange resin. Here, the average particle size of the ion exchange resin is not particularly limited, but is preferably 2 μm or more and 10 μm or less. Examples of cation exchange resins include sulfonated phenol-formaldehyde condensates, sulfonated phenol-benzaldehyde condensates, sulfonated styrene-divinylbenzene copolymers, sulfonated methacrylic acid-divinylbenzene copolymers, and other types of polymers containing sulfonic acid or carboxylic acid groups. The cation exchange resin includes H + Counter ion, NH4 + Counter ions, or alkali metal counter ions, e.g., K + and Na + Counter ions are provided. In addition, it is preferable that the cation exchange resin has hydrogen counter ions. As such a cation exchange resin, H +An example of a sulfonated styrene-divinylbenzene copolymer having counter ions is Purolite’s Microlite (registered trademark) PrCH. Such a cation exchange resin is commercially available as Rohm and Haas’s AMBERLYST (registered trademark).
[0116] In addition, the pore size of the filter is preferably 0.001 μm or larger, more preferably 0.005 μm or larger, and preferably 1 μm or smaller. If the pore size of the filter is within the above range, it is possible to sufficiently prevent impurities such as metals from being incorporated into the positive-type resist composition.
[0117] (Resist pattern formation kit for EUV lithography)
[0118] The EUV lithography resist pattern forming kit of the present invention comprises the above-described positive-type resist composition for EUV lithography and a developer, and can be used when forming a resist pattern using EUV lithography technology. Since the EUV lithography resist pattern forming kit of the present invention includes the above-described positive-type resist composition, when used in EUV lithography, fine resist patterns can be efficiently formed at high resolution.
[0119] <Developer>
[0120] The developer used in the EUV lithography resist pattern forming kit of the present invention is not particularly limited and can be appropriately selected according to the properties of the copolymer included in the positive-type resist composition described above. Specifically, when selecting the developer, it is preferable to select a developer that does not dissolve the resist film before EUV exposure, while being able to dissolve the exposed portion of the resist film after exposure. In addition, the developer may be used as a single type or two or more types may be mixed in any ratio.
[0121] And, as a developer, for example, hydrofluorocarbons such as 1,1,1,2,3,4,4,5,5,5-decafluoropentane (CF3CFHCFHCF2CF3), 1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorohexane, 1,1,1,2,2,3,4,5,5,5-decafluoropentane, 1,1,1,3,3-pentafluorobutane, 1,1,1,2,2,3,3,4,4-nonafluorohexane, 2,2-dichloro-1,1,1-trifluoroethane, 1,1-dichloro-1-fluoroethane, 1,1-dichloro-2,2,3,3,3-pentafluoropropane (CF3CF2CHCl2), Hydrochlorofluorocarbons such as 1,3-dichloro-1,1,2,2,3-pentafluoropropane (CClF2CF2CHClF), hydrofluoroethers such as methylnonafluorobutyl ether (CF3CF2CF2CF2OCH3), methylnonafluoroisobutyl ether, ethylnonafluorobutyl ether (CF3CF2CF2CF2OC2H5), ethylnonafluoroisobutyl ether, and perfluorohexylmethyl ether (CF3CF2CF(OCH3)C3F7), and CF4, C2F6, C3F8, C4F8, C4F 10 , C5F 12 , C6F 12 , C6F 14 , C7F 14 , C7F 16 , C8F 18 , C9F 20Fluorinated solvents such as perfluorocarbons; alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, and 1-hexanol; acetic acid esters having an alkyl group such as amyl acetate and hexyl acetate; a mixture of a fluorinated solvent and an alcohol; a mixture of a fluorinated solvent and an acetic acid ester having an alkyl group; a mixture of an alcohol and an acetic acid ester having an alkyl group; a mixture of a fluorinated solvent and an alcohol and an acetic acid ester having an alkyl group; etc. may be used. Among these, alcohol is preferred in terms of forming fine resist patterns more efficiently at high resolution by EUV lithography, alcohol having 2 to 6 carbon atoms is more preferred, ethanol, isopropyl alcohol, 1-butanol, 2-butanol, 1-pentanol, and 1-hexanol are even more preferred, and isopropyl alcohol is particularly preferred.
[0122] <Method for Forming a Resist Pattern Using a Resist Pattern Forming Kit>
[0123] The method for forming a resist pattern using the EUV lithography resist pattern forming kit of the present invention is not particularly limited and, for example, may be a method including the process described below.
[0124] [Resist Pattern Formation Method]
[0125] A method for forming a resist pattern using a resist pattern forming kit comprises, for example, a process of forming a resist film on a workpiece such as a substrate using a positive-type resist composition included in the resist pattern forming kit (resist film forming process), a process of exposing the resist film to EUV (exposure process), and a process of developing the exposed resist film using a developer included in the resist pattern forming kit (development process).
[0126] Meanwhile, a resist pattern formation method using a resist pattern formation kit may include processes other than the resist film formation process, exposure process, and development process described above. Specifically, the resist pattern formation method may include a process of forming a lower layer film on a substrate on which the resist film is formed (lower layer formation process) before the resist film formation process. In addition, the resist pattern formation method may further include a process of heating the exposed resist film (post-exposure bake process) between the exposure process and the development process. In addition, the resist pattern formation method may further include a process of removing the developer solution (rinsing process) after the development process. Furthermore, after forming a resist pattern by the resist pattern formation method, a process of etching the lower layer film and / or the substrate (etching process) may be performed.
[0127] -Circuit board-
[0128] Here, in the method for forming a resist pattern, the substrate capable of forming a resist film is not particularly limited and may include a substrate having an insulating layer and a copper foil formed on the insulating layer, which is used in the manufacture of printed circuit boards, etc., and mask blanks formed by forming a light-blocking layer on the substrate.
[0129] Examples of substrate materials include inorganic materials such as metal (silicon, copper, chromium, iron, aluminum, etc.), glass, titanium oxide, silicon dioxide (SiO2), silica, and mica; nitrides such as SiN; nitride oxides such as SiON; and organic materials such as acrylic, polystyrene, cellulose, cellulose acetate, and phenolic resin. Among these, metal is preferred as the substrate material. By using, for example, a silicon substrate, a silicon dioxide substrate, or a copper substrate, preferably a silicon substrate or a silicon dioxide substrate, as the substrate, a cylindrical structure can be formed.
[0130] In addition, the size and shape of the substrate are not particularly limited. Meanwhile, the surface of the substrate may be smooth, may have a curved or uneven shape, or may be a substrate with a thin sheet shape.
[0131] Additionally, surface treatment may be performed on the surface of the substrate as needed. For example, in the case of a substrate having hydroxyl groups on its surface layer, the surface of the substrate may be treated using a silane-based coupling agent capable of reacting with the hydroxyl groups. By doing so, the surface layer of the substrate can be changed from hydrophilic to hydrophobic, thereby increasing the adhesion between the substrate and the underlying film, or between the substrate and the resist layer. At this time, the silane-based coupling agent is not particularly limited, but hexamethyldisilazane is preferred.
[0132] -Sublayer formation process-
[0133] In the process of forming a lower layer, a lower layer is formed on a substrate. By forming a lower layer on the substrate, the surface of the substrate becomes hydrophobic. This increases the affinity between the substrate and the resist film, thereby increasing the adhesion between the substrate and the resist film. The lower layer may be an inorganic lower layer or an organic lower layer.
[0134] An inorganic underlayer can be formed by applying an inorganic material onto a substrate and performing processes such as firing. Examples of inorganic materials include silicon-based materials.
[0135] An organic underlayer can be formed by applying an organic material onto a substrate to form a film and drying it. The organic material is not limited to those sensitive to light or electron beams, and may use resist materials or resin materials commonly used in fields such as semiconductors and liquid crystals. Among these, it is preferable that the organic material be a material capable of forming an organic underlayer capable of etching, particularly dry etching. With such an organic material, the pattern of the underlayer can be formed by transferring the pattern to the underlayer by etching the organic underlayer using a pattern formed by processing a resist film. Among these, it is preferable that the organic material be a material capable of forming an organic underlayer capable of etching, such as oxygen plasma etching. Examples of organic materials used for forming the organic underlayer include AL412 from Brewer Science.
[0136] The coating of the aforementioned organic material can be performed by conventional known methods using a spin coat or a spinner. Furthermore, regarding the method for drying the coating film, any method capable of volatilizing the solvent contained in the organic material may be used, such as a baking method. At that time, the baking conditions are not particularly limited, but the baking temperature is preferably 80°C or higher and 300°C or lower, and more preferably 200°C or higher and 300°C or lower. In addition, the baking time is preferably 30 seconds or more, more preferably 60 seconds or more, preferably 500 seconds or less, more preferably 400 seconds or less, even more preferably 300 seconds or less, and particularly preferably 180 seconds or less. Furthermore, the thickness of the underlying film after drying the coating film is not particularly limited, but it is preferably 10 nm or more and 100 nm or less.
[0137] -Resist film formation process-
[0138] In the resist film formation process, a positive type resist composition included in the resist pattern forming kit of the present invention is used.
[0139] In the resist film formation process, a positive-type resist composition is applied to a workpiece, such as a substrate, that is processed using a resist pattern (or to the lower layer if a lower layer is formed), and the applied positive-type resist composition is dried to form a resist film.
[0140] In addition, the application and drying methods of the positive-type resist composition are not particularly limited, and methods generally used for forming resist films may be used. Among these, heating (pre-baking) is preferred as the drying method, and the pre-baking temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 140°C or higher from the viewpoint of improving the film density of the resist film, and is preferably 250°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower from the viewpoint of reducing changes in the molecular weight and molecular weight distribution of the copolymer in the resist film before and after pre-baking. In addition, the prebaking time is preferably 10 seconds or more, more preferably 20 seconds or more, and even more preferably 30 seconds or more in terms of improving the film density of the resist film formed through prebaking, and is preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less in terms of reducing changes in the molecular weight and molecular weight distribution of the copolymer in the resist film before and after prebaking.
[0141] -Photolithography Process-
[0142] In the photolithography process, EUV is irradiated onto the resist film formed in the resist film formation process to draw a desired pattern.
[0143] Meanwhile, the wavelength of the EUV to be irradiated is not particularly limited and, for example, can be 1 nm or more and 30 nm or less, and preferably 13.5 nm.
[0144] In addition, known exposure devices such as the EQ-10M (manufactured by ENERGETIQ) and NXE (manufactured by ASML) can be used for EUV irradiation.
[0145] -Post-exposure bake process-
[0146] In an optional post-exposure bake process, the resist film exposed in the exposure process is heated. By performing the post-exposure bake process, the surface roughness of the resist pattern can be reduced.
[0147] Here, the heating temperature is preferably 70°C or higher, more preferably 80°C or higher, even more preferably 90°C or higher, preferably 200°C or lower, more preferably 170°C or lower, and even more preferably 150°C or lower. If the heating temperature is within the above range, the surface roughness of the resist pattern can be effectively reduced while increasing the clarity of the resist pattern.
[0148] In addition, the heating time (heating time) for the resist film in the post-exposure bake process is preferably 10 seconds or more, more preferably 20 seconds or more, and even more preferably 30 seconds or more. If the heating time is 10 seconds or more, the surface roughness of the resist pattern can be sufficiently reduced while increasing the clarity of the resist pattern. On the other hand, from the perspective of production efficiency, the heating time is preferably, for example, 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less.
[0149] In addition, the method of heating the resist film in the post-exposure bake process is not particularly limited, and examples include heating the resist film with a hot plate, heating the resist film in an oven, or blowing hot air onto the resist film.
[0150] -Current Process-
[0151] In the development process, the resist film exposed in the photolithography process (or the exposed and heated resist film in the case where a post-exposure bake process was performed) is brought into contact with the developer included in the resist pattern forming kit to develop the resist film and form a resist pattern on the workpiece.
[0152] Here, the method of bringing the resist film into contact with the developer is not particularly limited, and known methods such as immersion of the resist film into the developer or application of the developer to the resist film may be used.
[0153] Meanwhile, the temperature of the developing solution during development is not specifically limited, but can be, for example, 21°C or higher and 25°C or lower. In addition, the development time can be, for example, 15 seconds or higher and 4 minutes or lower.
[0154] When developed using the developer included in the resist pattern forming kit of the present invention, a fine resist pattern can be efficiently formed at high resolution.
[0155] -Rinsing Process-
[0156] In the rinsing process, the resist film developed in the developing process is brought into contact with the rinsing liquid to rinse the developed resist film and form a resist pattern on the workpiece.
[0157] Here, the method of bringing the developed resist film into contact with the rinse solution is not particularly limited, and known methods such as immersion of the resist film in the rinse solution or application of the rinse solution to the resist film can be used.
[0158] As for the rinsing solution, any rinsing solution is not particularly limited and can be used as long as it is capable of removing residue of the developer or resist attached to the developed resist film.
[0159] Meanwhile, the temperature of the rinse solution during rinsing is not specifically limited, but can be, for example, 21°C or higher and 25°C or lower. In addition, the rinsing time can be, for example, 5 seconds or higher and 3 minutes or lower.
[0160] The above-described developer and rinse solutions may each be filtered before use. As for the filtration method, for example, the filtration method using a filter described in the above-described section "Preparation of a positive-type resist composition" may be cited.
[0161] -Etching Process-
[0162] In the etching process, the lower layer film and / or substrate are etched using the above-described resist pattern as a mask to form a pattern on the lower layer film and / or substrate.
[0163] At that time, the number of etching cycles is not particularly limited and may be one or multiple. In addition, the etching may be dry etching or wet etching, but dry etching is preferred. Dry etching can be performed using a known dry etching apparatus. The etching gas used for dry etching can be appropriately selected according to the elemental composition of the underlying film or substrate to be etched. As etching gases, for example, fluorine-based gases such as CHF3, CF4, C2F6, C3F8, SF6; chlorine-based gases such as Cl2, BCl3; oxygen-based gases such as O2, O3, H2O; reducing gases such as H2, NH3, CO, CO2, CH4, C2H2, C2H4, C2H6, C3H4, C3H6, C3H8, HF, HI, HBr, HCl, NO, NH3, BCl3, etc. Examples include inert gases such as He, N2, and Ar. These gases may be used individually or in a mixture of two or more types. Meanwhile, oxygen-based gases are typically used for the dry etching of inorganic underlying films. Additionally, fluorine-based gases are typically used for the dry etching of substrates, and a mixture of fluorine-based gases and inert gases is suitable for use.
[0164] Additionally, if necessary, the underlying layer remaining on the substrate may be removed before or after etching the substrate. When removing the underlying layer before etching the substrate, the underlying layer may be a patterned underlying layer or an unpatterned underlying layer.
[0165] Here, methods for removing the lower film include, for example, the dry etching described above. In addition, in the case of an inorganic lower film, the lower film may be removed by contacting the lower film with a liquid such as a basic solution or an acidic solution, preferably a basic liquid. Here, the basic solution is not particularly limited and may include, for example, alkaline hydrogen peroxide. A method for removing the lower film by wet stripping using alkaline hydrogen peroxide is not particularly limited as long as the lower film and the alkaline hydrogen peroxide can come into contact for a certain period of time under heating conditions, and may include, for example, a method of immersing the lower film in heated alkaline hydrogen peroxide, a method of spraying alkaline hydrogen peroxide onto the lower film under a heating environment, or a method of coating the lower film with heated alkaline hydrogen peroxide. After performing any one of these methods, the substrate can be washed with water and dried to obtain a substrate from which the lower film has been removed.
[0166] Hereinafter, an example of a method for forming a resist pattern using the resist pattern forming kit of the present invention, and a method for etching an underlayer film and a substrate using the formed resist pattern, will be described. However, since the substrate and conditions in each process used in the following example can be the same as those described above regarding the substrate and conditions in each process, the description below will be omitted. On the other hand, the method for forming a resist pattern using the resist pattern forming kit of the present invention is not limited to the method shown in the following example.
[0167] An example of a resist pattern formation method is a resist pattern formation method using EUV, comprising the above-described lower layer formation process, resist film formation process, exposure process, development process, and rinsing process. Additionally, an example of an etching method is to use the resist pattern formed by the resist pattern formation method as a mask, and includes an etching process.
[0168] Specifically, in the process of forming a lower layer, an inorganic lower layer is formed by applying an inorganic material onto a substrate and performing firing.
[0169] Next, in the resist film formation process, a resist composition included in the resist pattern forming kit of the present invention is applied onto the inorganic lower film formed in the lower film formation process and dried to form a resist film.
[0170] Then, in the photolithography process, EUV is irradiated onto the resist film formed in the resist film formation process to draw a desired pattern.
[0171] In addition, in the development process, the resist film exposed in the photolithography process is brought into contact with the developer included in the resist pattern forming kit of the present invention to develop the resist film and form a resist pattern on the lower film.
[0172] And, in the rinsing process, the developed resist film from the developing process is brought into contact with the rinsing liquid to rinse the developed resist film.
[0173] Then, in the etching process, the lower layer is etched using the resist pattern as a mask to form a pattern on the lower layer.
[0174] Next, the substrate is etched using the patterned lower layer film as a mask to form a pattern on the substrate.
[0175] Examples
[0176] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. Meanwhile, in the following description, "%" indicating amount is based on mass unless otherwise specified.
[0177] In addition, in the examples and comparative examples, the weight average molecular weight, number average molecular weight, and molecular weight distribution of the copolymer, the ratio of each molecular weight component in the copolymer, the optimal exposure amount, CD value, LWR value, LER value, and LCDU value were measured by the following method.
[0178] <Weight-average molecular weight, number-average molecular weight, and molecular weight distribution>
[0179] For the copolymers obtained in the examples and comparative examples, the weight-average molecular weight (Mw) and number-average molecular weight (Mn) were measured using gel permeation chromatography, and the molecular weight distribution (Mw / Mn) was calculated. Specifically, gel permeation chromatography (HLC-8220 manufactured by Tosho Co., Ltd.) was used, and tetrahydrofuran was used as the developing solvent to determine the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the polymer as standard polystyrene equivalent values. Then, the molecular weight distribution (Mw / Mn) was calculated.
[0180] <Ratio of components of each molecular weight in the copolymer>
[0181] A chromatogram of the copolymer was obtained using gel permeation chromatography (Tosho, HLC-8220) and tetrahydrofuran as the developing solvent. From the obtained chromatogram, the total peak area (A), the sum of peak areas of components with a molecular weight of less than 10,000 (B), the sum of peak areas of components with a molecular weight of less than 50,000 (C), the sum of peak areas of components with a molecular weight of less than 100,000 (D), and the sum of peak areas of components with a molecular weight greater than 200,000 (E) were calculated. Then, the ratio of each molecular weight component was calculated using the following formula.
[0182] Percentage of components with a molecular weight less than 10,000 (%) = (B / A) × 100
[0183] Percentage of components with a molecular weight less than 50,000 (%) = (C / A) × 100
[0184] Percentage of components with a molecular weight less than 100,000 (%) = (D / A) × 100
[0185] Percentage of components with a molecular weight exceeding 200,000 (%) = (E / A) × 100
[0186] <Optimal exposure amount (E op )>
[0187] Optimal exposure amount (E op ) was obtained by shaking the exposure amount and focus as the best point from the CD value, LER value, and LWR value.
[0188] <CD값, LWR값, LER값, LCDU값>
[0189] The CD value, LWR value, LER value, and LCDU value of the resist pattern formed in the examples and comparative examples were measured and calculated using a high-resolution FEB measuring device (manufactured by Hitachi High Technology Co., Ltd., CG5000) and analysis software (manufactured by Hitachi High Technology Co., Ltd., Design Metrology System).
[0190] A CD value within the range of half pitch (hp) or contact hole ±5nm, and lower LWR, LER, and LCDU values indicate higher resolution of the resist pattern.
[0191] (Example 1)
[0192] Preparation of copolymers
[0193] [Synthesis of Polymers]
[0194] A monomer composition comprising 3.00 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a), 2.493 g of α-methylstyrene as monomer (b), and 2.833 g of cyclopentanone as solvent was added to a glass ampoule containing a stirrer, sealed, and oxygen in the system was removed by repeating pressurization and depressurization with nitrogen gas 10 times.
[0195] Then, the system was heated to 50°C and the reaction was carried out for 25 hours. Next, 10 g of tetrahydrofuran was added to the system, and the resulting solution was added dropwise to 300 mL of methanol to precipitate the polymer. Afterward, the precipitated polymer was recovered by filtration. Meanwhile, the obtained polymer was a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units.
[0196] [Purification of Polymers]
[0197] Subsequently, the polymer recovered by filtration was dissolved in 10 g of tetrahydrofuran (THF), and the resulting solution was added dropwise to 100 g of a mixed solvent of THF and methanol (MeOH) (THF:MeOH (mass ratio) = 27:73) to precipitate a white coagulated product (a copolymer containing α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units). Subsequently, the solution containing the precipitated copolymer was filtered using a Kiriyama funnel to obtain a white copolymer (a copolymer containing 50 mol% each of α-methylstyrene units (AMS units) and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units (ACAFPh units)).
[0198] For the obtained copolymer, the weight-average molecular weight, number-average molecular weight, and molecular weight distribution were measured. The results are shown in Table 1.
[0199] <Preparation of a Positive-Type Resist Composition>
[0200] The obtained copolymer was dissolved in isoamyl acetate as a solvent to prepare a resist solution (positive type resist composition) with a copolymer concentration of 11 mass%.
[0201] Formation of Resist Pattern
[0202] AL412 (manufactured by Brewer Science) was applied as a sublayer on a 4-inch diameter silicon wafer using a spin coater (Mikasa MS-A150). The applied AL412 was then heated on a hot plate at 205°C for 1 minute to form a sublayer with a thickness of 20 nm on the silicon wafer. Subsequently, the obtained positive-type resist composition was applied onto the sublayer. The applied positive-type resist composition was then heated on a hot plate at 150°C for 3 minutes to form a resist film with a thickness of 33 nm or 50 nm on the silicon wafer. Finally, using an EUV lithography device (ASML TWINSCAN NXE:3400B), the resist film was... at an optimal exposure dose (E op A pattern was drawn by exposure to light. Then, isopropyl alcohol (IPA) was used as the developer, and a development treatment was performed at a temperature of 23°C for 30 seconds to form a resist pattern. At that time, the lines (unexposed areas) and spaces (exposed areas) of the resist pattern were each set to lines and spaces of 16 nm (i.e., half pitch (hp) 16 nm).
[0203] Using the obtained resist pattern, the CD value, LWR value, and LER value were measured. The results are shown in Table 1.
[0204] (Example 2)
[0205] During the synthesis of the polymer, the reaction was carried out at a temperature of 30°C for 80 hours. At the same time as in Example 1, the copolymer was prepared, the positive resist composition was prepared, and the resist pattern was formed, in the same manner as in Example 1, except that the composition of the mixed solvent used for the purification of the polymer (THF:MeOH (mass ratio)) was set to 29:71. Various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0206] (Example 3)
[0207] Except for preparing the copolymer as described below, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0208] Preparation of copolymers
[0209] [Preparation of an aqueous solution with an 18% solid content of semi-cured beef tallow fatty acid potassium soap]
[0210] 100g of ion-exchanged water was prepared and heated to 70℃ while stirring, and 8.40g of potassium hydroxide (49% aqueous solution) was added. Next, 19.6g of beef tallow 45° hardened fatty acid HFA (manufactured by Nichiyu Co., Ltd.) was added at an addition rate of 1.28 g / min, and then 0.126g of potassium silicate was added. The mixture was then stirred at 80℃ for more than 2 hours to obtain an aqueous solution of semi-hardened beef tallow fatty acid potassium soap with a solid content of 18%.
[0211] [Synthesis of Polymers]
[0212] 3.00 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a) and 2.712 g of α-methylstyrene as monomer (b) were added to a glass ampoule containing a stirrer. Additionally, 6.771 g of ion-exchanged water was added to 0.5463 g of an aqueous solution of semi-cured beef tallow fatty acid potassium soap with a solid content of 18% prepared above, and the monomer composition was formed. Then, the ampoule was sealed, and oxygen in the system was removed by repeating pressurization and depressurization with nitrogen gas 10 times.
[0213] Then, the system was heated to 40°C, and the polymerization reaction was carried out for 11 hours. Next, 10 g of tetrahydrofuran was added to the system, and the resulting solution was added dropwise to 300 mL of methanol to precipitate the polymer. Afterward, the precipitated polymer was recovered by filtration. Meanwhile, the obtained polymer was a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units.
[0214] [Purification of Polymers]
[0215] The polymer recovered by filtration was dissolved in 10 g of tetrahydrofuran (THF), and the resulting solution was added dropwise to 100 g of a mixed solvent of THF and methanol (MeOH) (THF:MeOH (mass ratio) = 35:65) to precipitate a white coagulated product (a copolymer containing α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units). Subsequently, the solution containing the precipitated copolymer was filtered through a Kiriyama funnel to obtain a white copolymer (a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units).
[0216] For the obtained copolymer, the weight-average molecular weight, number-average molecular weight, and molecular weight distribution were measured. The results are shown in Table 1.
[0217] (Example 4)
[0218] Except for using ethanol (EtOH) as the developer when forming the resist pattern, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 3, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0219] (Example 5)
[0220] 3.034 g of 4-methyl-α-methylstyrene (4-isopropphenyltoluene) was used instead of α-methylstyrene during the synthesis of the polymer, and the reaction was carried out at a temperature of 50°C for 6 hours. At the same time, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were performed in the same manner as in Example 3, except that the composition of the mixed solvent used during the purification of the polymer (THF:MeOH (mass ratio)) was set to 30:70. Various evaluations were then performed in the same manner as in Example 1. The results are shown in Table 1.
[0221] (Example 6)
[0222] Except for using 3.034 g of 4-methyl-α-methylstyrene (4-isopropphenyltoluene) instead of α-methylstyrene during the synthesis of the polymer and setting the composition of the mixed solvent used during the purification of the polymer (THF:MeOH (mass ratio)) to 33:67, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.
[0223] (Examples 7-9)
[0224] During the synthesis of the polymer, the amounts of α-methylstyrene were set to 2.132 g (Example 7), 1.599 g (Example 8), and 1.066 g (Example 9), respectively, and the amounts of cyclopentanone were set to 2.199 g (Example 7), 1.971 g (Example 8), and 1.743 g (Example 9), respectively. The reaction was carried out at a temperature of 30°C for 50 hours. At the same time, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were performed in the same manner as in Example 1, except that the composition of the mixed solvent used for the purification of the polymer (THF:MeOH (mass ratio)) was set to 30:70. Various evaluations were then performed in the same manner as in Example 1. The results are shown in Table 1.
[0225] (Example 10)
[0226] Except for using ethanol as the developer when forming the resist pattern, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 9, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0227] (Example 11)
[0228] During the synthesis of the polymer, the amount of α-methylstyrene was set to 0.5329 g and the amount of cyclopentanone to 1.514 g, and the reaction was carried out at a temperature of 30°C for 50 hours. At the same time, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were performed in the same manner as in Example 1, except that the composition of the mixed solvent used during the purification of the polymer (THF:MeOH (mass ratio)) was set to 30:70. Various evaluations were then performed in the same manner as in Example 1. The results are shown in Table 1.
[0229] (Examples 12 to 15)
[0230] Except for synthesizing the polymer, the amount of α-methylstyrene was set to 1.066 g, and the temperature and time of the polymerization reaction were set to 70°C for 6 hours (Example 12), 60°C for 6 hours (Example 13), 50°C for 6 hours (Example 14), and 40°C for 11 hours (Example 15), respectively, and the composition of the mixed solvent (THF:MeOH (mass ratio)) used for purifying the polymer was set to 30:70 (Example 12), 32:68 (Example 13), 34:66 (Example 14), and 34:66 (Example 15), respectively, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 3, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0231] (Example 16)
[0232] Except for using ethanol as the developer during the formation of the resist pattern, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 15, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0233] (Example 17)
[0234] Except for using 2-butanol (2-BtOH) as the developer when forming the resist pattern, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 3, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0235] (Example 18)
[0236] Except for using 2-butanol as the developer when forming the resist pattern, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 9, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0237] (Example 19)
[0238] Except for using 2-butanol as the developer when forming the resist pattern, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 15, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0239] (Example 20)
[0240] Except for synthesizing the polymer, the polymerization reaction temperature and time were set to 75°C for 1 hour, and the composition of the mixed solvent used for purifying the polymer (THF:MeOH (mass ratio)) was set to 30:70, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.
[0241] (Example 21)
[0242] Except for purifying the polymer as described below, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 20, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0243] [Purification of Polymers]
[0244] The polymer recovered by filtration was dissolved in 10 g of tetrahydrofuran (THF), and the resulting solution was added dropwise to 100 g of a mixed solvent of THF and methanol (MeOH) (THF:MeOH (mass ratio) = 30:70) to precipitate a white coagulated product. Next, the solution containing the precipitated coagulated product was filtered through a Kiriyama funnel, and the resulting white coagulated product was dissolved again in 10 g of tetrahydrofuran (THF). The resulting solution was added dropwise to 100 g of a mixed solvent for re-purification (THF:MeOH (mass ratio) = 30:70) to precipitate a white re-coagulated product (a copolymer containing α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units) (re-purification). Afterwards, the solution containing the precipitated copolymer was filtered through a Kiriyama funnel to obtain a white copolymer (a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units).
[0245] (Examples 22-25)
[0246] Except for the composition (THF:MeOH (mass ratio)) of the mixed solvent for re-purification used during the purification of the polymer being 31:39 (Example 22), 32:68 (Example 23), 33:67 (Example 24), and 34:66 (Example 25), respectively, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.
[0247] (Example 26)
[0248] Except for purifying the polymer as described below, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 20, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0249] [Purification of Polymers]
[0250] The polymer recovered by filtration was dissolved in 10g of tetrahydrofuran (THF), and the resulting solution was added dropwise to 100g of a mixed solvent of THF and methanol (MeOH) (THF:MeOH (mass ratio) = 30:70) to precipitate a white coagulated product. Next, the solution containing the precipitated coagulated product was filtered through a Kiriyama funnel, and the resulting white coagulated product was dissolved again in 10g of tetrahydrofuran (THF). The resulting solution was added dropwise to 100g of a mixed solvent for re-purification (THF:MeOH (mass ratio) = 33:67) to precipitate a white re-coagulated product (re-purification). In addition, the solution containing the precipitated re-coagulated product was filtered through a Kiriyama funnel, and the resulting white re-coagulated product was dissolved again in 10g of tetrahydrofuran (THF). The obtained solution was added dropwise to 100 g of a mixed solvent for re-purification (THF:MeOH (mass ratio) = 33:67) to precipitate a white re-coagulated product (a copolymer containing α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units) (re-purification). Subsequently, the solution containing the precipitated copolymer was filtered through a Kiriyama funnel to obtain a white copolymer (a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units).
[0251] (Examples 27–33)
[0252] Except for the amount of α-methylstyrene being 1.066 g during the synthesis of the polymer, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Examples 20 to 26, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0253] (Comparative Example 1)
[0254] During the synthesis of the polymer, 0.003953 g of azobis-isobutyronitrile was added to the monomer composition as a polymerization initiator and reacted at 78°C for 3.5 hours without using cyclopentanone. In addition, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, except that the polymer was not purified. Various evaluations were then performed in the same manner as in Example 1. The results are shown in Table 3.
[0255] (Comparative Example 2)
[0256] During the synthesis of the polymer, 0.003953 g of azobis-isobutyronitrile was added to the monomer composition as a polymerization initiator and reacted at 78°C for 3.5 hours without using cyclopentanone. At the same time, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, except that the composition of the mixed solvent used during the purification of the polymer (THF:MeOH (mass ratio)) was set to 20:80. Various evaluations were then performed in the same manner as in Example 1. The results are shown in Table 3.
[0257] (Comparative Example 3)
[0258] Except for preparing the copolymer and forming the resist pattern as described below, the preparation of the copolymer, preparation of the positive-type resist composition, and formation of the resist pattern were carried out in the same manner as in Example 1, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0259] Preparation of copolymers
[0260] [Synthesis of Polymers]
[0261] A monomer composition comprising 3.00 g of α-chloroacrylate pentafluoropropyl as a monomer, 3.476 g of α-methylstyrene as a monomer (b), 0.005513 g of azobisisobutyronitrile as a polymerization initiator, and 1.620 g of cyclopentanone as a solvent was added to a glass ampoule containing a stirrer, sealed, and oxygen in the system was removed by repeating pressurization and depressurization with nitrogen gas 10 times.
[0262] Then, the system was heated to 78°C and the reaction was carried out for 6 hours. Next, 10 g of tetrahydrofuran was added to the system, and the resulting solution was added dropwise to 300 mL of methanol to precipitate the polymer. Afterward, the precipitated polymer was recovered by filtration. Meanwhile, the obtained polymer was a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylate pentafluoropropyl units.
[0263] [Purification of Polymers]
[0264] Subsequently, the polymer recovered by filtration was dissolved in 10 g of tetrahydrofuran (THF), and the resulting solution was added dropwise to 100 g of a mixed solvent of THF and methanol (MeOH) (THF:MeOH (mass ratio) = 15:85) to precipitate a white coagulated product (a copolymer containing α-methylstyrene units and α-chloroacrylate pentafluoropropyl units). Subsequently, the solution containing the precipitated copolymer was filtered through a Kiriyama funnel to obtain a white copolymer (a copolymer containing 50 mol% each of α-methylstyrene units and α-chloroacrylate pentafluoropropyl units (ACAPFP units)).
[0265] Formation of Resist Pattern
[0266] AL412 (manufactured by Brewer Science) was applied as a sublayer on a 4-inch diameter silicon wafer using a spin coater (MS-A150 manufactured by Mikasa). Then, the applied AL412 was heated on a hot plate at a temperature of 205°C for 1 minute to form a sublayer with a thickness of 20 nm on the silicon wafer. After that, the obtained positive resist composition was applied onto the sublayer. Then, the applied positive resist composition was heated on a hot plate at a temperature of 150°C for 3 minutes to form a resist film with a thickness of 33 nm or 50 nm on the silicon wafer. Then, using an EUV lithography device (TWINSCAN NXE:3400B manufactured by ASML), the resist film was exposed to an optimal exposure amount (Eop) to draw a pattern. Subsequently, a development treatment was performed for 30 seconds at a temperature of 23°C using hydrofluorocarbon (HFC: manufactured by Mitsui DuPont Fluorochemicals, Inc., Butrel XF (CF3CFHCFHCF2CF3)) as the developer. Then, a resist pattern was formed by rinsing for 10 seconds at a temperature of 23°C using hydrofluoroether (HFE: manufactured by 3M, Novec (registered trademark) 7100 (C4F9OCH3)) as the rinse solution. At that time, the lines (unexposed areas) and spaces (exposed areas) of the resist pattern were each set to lines and spaces of 16 nm (i.e., half pitch (hp) 16 nm).
[0267] (Comparative Examples 4 ~ 6)
[0268] During the synthesis of the polymer, the amount of α-methylstyrene was set to 3.283 g (Comparative Example 4), 3.468 g (Comparative Example 5), and 3.468 g (Comparative Example 6), respectively; the amount of azobisisobutyronitrile was set to 0.0005207 g (Comparative Example 4), 0.002065 g (Comparative Example 5), and 0.001377 g (Comparative Example 6), respectively; the amount of cyclopentanone was set to 1.571 g (Comparative Example 4), 6.466 g (Comparative Example 5), and 6.467 g (Comparative Example 6), respectively; and the temperature and time of the polymerization reaction were set to 78°C for 2 hours (Comparative Example 4), 53°C for 50 hours (Comparative Example 5), and 40°C for 50 hours (Comparative Example 6), respectively; and at the same time, the polymer Except for the composition of the mixed solvent used during purification (THF:MeOH (mass ratio)) being 21:79 (Comparative Example 4), 24:76 (Comparative Example 5), and 26:74 (Comparative Example 6), respectively, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were carried out in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 3.
[0269] (Comparative Example 7)
[0270] During the synthesis of the polymer, 0.003953 g of azobis-isobutyronitrile was added to the monomer composition as a polymerization initiator, the amount of cyclopentanone was set to 1.380 g, and the reaction was carried out at 78°C for 6 hours. Except for not purifying the polymer, the preparation of the copolymer, the preparation of the positive-type resist composition, and the formation of the resist pattern were performed in the same manner as in Example 1, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0271]
[0272]
[0273]
[0274] From Tables 1 to 3, it can be seen that in Examples 1 to 33, fine resist patterns can be efficiently formed at high resolution compared to Comparative Examples 1 to 7.
[0275] Industrial applicability
[0276] According to the present invention, it is possible to efficiently form fine resist patterns at high resolution in EUV lithography technology.
Claims
Claim 1 Formula (I) below: [Chemical Formula 1] A monomer unit (A) represented by [wherein X is a halogen atom, a cyano group, an alkylsulfonyl group, an alkoxy group, a nitro group, an acyl group, an alkyl ester group, or an alkyl halide group, L is a single bond or a divalent linker, and Ar is an aromatic ring that may have a substituent] and the following formula (II): [Chemical Formula 2] [In Equation (II), R 1 It is an alkyl group, and R 2 is an alkyl group, a halogen atom, an alkyl halide, a hydroxyl group, a carboxyl group, or a carboxyl halide, and p is an integer between 0 and 5 inclusive, and R 2 A positive-type resist composition for extreme ultraviolet lithography comprising a copolymer having a weight average molecular weight greater than 100,000, wherein the copolymer has a monomer unit (B) represented as [where multiple units exist, they may be identical or different from each other], and wherein the copolymer has a ratio of a component with a molecular weight less than 100,000 of 30% or less and a ratio of a component with a molecular weight greater than 200,000 of 8.0% or more and 95% or less. Claim 2 A positive resist composition for extreme ultraviolet lithography according to claim 1, wherein the monomer unit (A) is an α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl unit and the monomer unit (B) is an α-methylstyrene unit or a 4-methyl-α-methylstyrene unit. Claim 3 A positive resist composition for extreme ultraviolet lithography according to claim 1, wherein the copolymer has a content ratio of the monomer unit (A) of more than 50 mol% and less than or equal to 60 mol%, and a content ratio of the monomer unit (B) of more than 40 mol% and less than or equal to 50 mol%. Claim 4 A positive resist composition for extreme ultraviolet lithography according to claim 1, wherein the molecular weight distribution (Mw / Mn) of the copolymer is 1.20 or more and 1.60 or less. Claim 5 The copolymer of claim 1 is a positive-type resist composition for extreme ultraviolet lithography, wherein the proportion of a component having a molecular weight of less than 10,000 is less than 1.5%. Claim 6 The copolymer of claim 1 is a positive-type resist composition for extreme ultraviolet lithography, wherein the proportion of a component having a molecular weight of less than 50,000 is less than 30%. Claim 7 A resist pattern forming kit for extreme ultraviolet lithography comprising a positive type resist composition for extreme ultraviolet lithography described in any one of claims 1 to 6 and a developer. Claim 8 A resist pattern forming kit for extreme ultraviolet lithography according to claim 7, wherein the developer is an alcohol. Claim 9 A resist pattern forming kit for extreme ultraviolet lithography according to claim 8, wherein the number of carbon atoms of the alcohol is 2 or more and 6 or less. Claim 10 delete Claim 11 delete
Citation Information
Patent Citations
Method for forming positive resist pattern
JP1989049039A
Polyacrylic acid derivative
JP1989215812A
Resist pattern forming method
JP2020052144A
Positive resist composition for EUV lithography and method for forming a resist pattern
KR1020210005570A
Copolymer and positive resist composition
KR1020210064190A